2022
DOI: 10.1111/clr.13914
|View full text |Cite
|
Sign up to set email alerts
|

Non‐surgical peri‐implantitis treatment with or without systemic antibiotics: a randomized controlled clinical trial

Abstract: Objectives: To assess the adjunctive effect of systemic amoxicillin (AMX) and metronidazole (MTZ) in patients receiving non-surgical treatment (NST) for peri-implantitis (PI). Materials and methods:Thirty-seven patients were randomized into an experimental group treated with NST plus AMX + MTZ (N = 18) and a control group treated with NST alone (N = 19). Clinical parameters were evaluated at 12 weeks post-treatment.The primary outcome was the change in peri-implant pocket depth (PIPD) from baseline to 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 54 publications
0
30
1
Order By: Relevance
“…Smoking habits were described in all studies and two of them included only no smokers [ 25 ] or light smokers [ 16 ]. History of periodontal disease was recorded in three studies [ 17 , 26 , 27 ] and the groups were comparable at baseline. Implant type was not described in two studies [ 17 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Smoking habits were described in all studies and two of them included only no smokers [ 25 ] or light smokers [ 16 ]. History of periodontal disease was recorded in three studies [ 17 , 26 , 27 ] and the groups were comparable at baseline. Implant type was not described in two studies [ 17 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Implant type was not described in two studies [ 17 , 25 ]. One study reported the use of implants with rough surfaces [ 28 ]; other types of implants were included in the other three studies, where implant brand, but not the implant surface, was specified [ 16 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This added value of adjunctive systemic antibiotics has also been demonstrated in periimplantitis regenerative interventions [ 53 ], with beneficial effects maintained up to 5 years postoperatively in patients with adequate supportive therapy [ 33 , 52 ]. There is only one randomized clinical trial demonstrating that this adjunctive application has a significant short-term advantage versus the placebo when used on moderately rough surface implants [ 36 ], and its real impact on the peri-implant microbiota is presently unknown [ 18 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%